2004
DOI: 10.1177/1049731504265837
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of PTSD on Treatment Adherence, Drug Relapse, and Criminal Recidivism in a Sample of Incarcerated Men and Women

Abstract: Objective/Method: Given the relationship between post-traumatic stress disorder (PTSD) and substance use disorders (SUD), and the prevalence of SUD among offenders, the inattention to trauma before, during, and after incarceration is troubling. This exploratory study compared those with and without co-occurring PTSD among men (n = 139) and women (n = 60) involved in prison-based substance abuse treatment. Results: More than one half the sample met criteria for lifetime PTSD with women experiencing a greater nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 36 publications
5
92
0
Order By: Relevance
“…In humans, it has been repeatedly reported that individuals that are comorbid for PTSD and SUDs do not differ from individuals with SUDs alone in substance use severity (Brown Stout and Mueller 1999;Eggleston et al 2009), but are more likely to relapse (Tate Brown Unrod and Ramo 2004;Kubiak 2004;Burns et al 2010;Najt Fusar-Poli and Brambilla 2011). This is corroborated by the findings in our experiments of no differences in acquisition or maintenance between previously shocked or unshocked rats, but shocked rats showed greater reinstatement after successful extinction.…”
Section: Discussionsupporting
confidence: 82%
“…In humans, it has been repeatedly reported that individuals that are comorbid for PTSD and SUDs do not differ from individuals with SUDs alone in substance use severity (Brown Stout and Mueller 1999;Eggleston et al 2009), but are more likely to relapse (Tate Brown Unrod and Ramo 2004;Kubiak 2004;Burns et al 2010;Najt Fusar-Poli and Brambilla 2011). This is corroborated by the findings in our experiments of no differences in acquisition or maintenance between previously shocked or unshocked rats, but shocked rats showed greater reinstatement after successful extinction.…”
Section: Discussionsupporting
confidence: 82%
“…Research also suggests that the high incidence of drug-related crimes and substance abuse, combined with the extensive trauma histories of women, is largely responsible for high recidivism rates (Bill, 1998;Garcia-Coll et al, 1997;Kubiak, 2004).…”
Section: Trauma Andsubstance Abuse Among Incarcerated Women Prevalencementioning
confidence: 99%
“…Several researchers have taken the theoretical position that the high incidence of drugrelated crimes and substance abuse, combined with inadequate treatment for the extensive trauma histories of women in prison, is largely responsible for high recidivism rates (Bill, 1998;Garcia-Coll et al, 1997;Kubiak, 2004;Zlotnick et al, 2003). Previous research, focusing on the prevalence of traumatic events in the lives of incarcerated women, found that 78% to 85% of these women experienced at least one trauma in their lifetimes (Browne et al, 1999;Pomeroy, 1998;Kane & DiBartolo, 2002).…”
Section: Restatement Ofthe Problemmentioning
confidence: 99%
“…Furthermore, Kubiak (2004) investigated the effects of PTSD on outcomes for incarcerated men and women who were involved in a prison rehabilitation program. Although men with PTSD were more likely to enter community aftercare treatment than those without PTSD, drug screens after release from prison showed a significantly higher rate of drug relapse and a higher rate of recidivism in those with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD is known to influence treatment adherence rates, with higher levels of PTSS being predictive of both lower adherence to treatment, and lower treatment retention (Najavits & Hien, 2013;Kubiak, 2004) Furthermore, higher levels of PTSS predict substance use relapse (Norman, Take, Anderson, & Brown, 2007;Ford, Hawke, Alessi, Ledgerwood, & Petry, 2007). This influence on treatment and relapse makes PTSD prohibitive of successful SUD treatment, especially as time spent in treatment is one of the only known predictors of treatment success in drug and alcohol rehabilitation (Hubbard, Craddock, & Anderson, 2003).…”
Section: Treating Ptsd and Sud Concurrentlymentioning
confidence: 99%